2019
DOI: 10.1038/s41409-019-0728-5
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of the inactivated influenza vaccine in children who have undergone allogeneic haematopoietic stem cell transplant

Abstract: Influenza vaccination is recommended for children following allogeneic haematopoietic stem cell transplant (HSCT), however there is limited evidence regarding its benefit. A prospective multicentre study was conducted to evaluate the immunogenicity of the inactivated influenza vaccine in children who have undergone HSCT compared with healthy agematched controls. Participants were vaccinated between 2013 and 2016 according to Australian guidelines. Influenzaspecific hemagglutinin inhibition antibody titres were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…8 There is a paucity of data regarding COVID-19 vaccination in children with cancer; however, these findings have been mirrored by studies of inactivated influenza and pneumococcal vaccination, which reflect that children with cancer are able to mount protective immune responses to vaccination, and that the extent of response is modulated by a variety of factors that can include the number of doses received, whether treatment is being delivered for a solid or hematological malignancy and lymphocyte count at the time of vaccination. [9][10][11] Given that the patterns of response are reflective of host immunity, similar outcomes are likely to be found following COVID-19 vaccination in children with cancer, suggesting that optimization of outcome could be achieved by timing immunization at the furthest point from the immunosuppressing effect of cytotoxic treatment during a given cycle. In addition, a specific consideration to vaccination of children with acute lymphoblastic leukemia is the presence of polyethylene glycol (PEG) as a stabilizing component of mRNA COVID-19 vaccines, necessitating the development and validation of strategies to mitigate risk for children with a prior history of hypersensitivity to PEGasparaginase.…”
mentioning
confidence: 89%
“…8 There is a paucity of data regarding COVID-19 vaccination in children with cancer; however, these findings have been mirrored by studies of inactivated influenza and pneumococcal vaccination, which reflect that children with cancer are able to mount protective immune responses to vaccination, and that the extent of response is modulated by a variety of factors that can include the number of doses received, whether treatment is being delivered for a solid or hematological malignancy and lymphocyte count at the time of vaccination. [9][10][11] Given that the patterns of response are reflective of host immunity, similar outcomes are likely to be found following COVID-19 vaccination in children with cancer, suggesting that optimization of outcome could be achieved by timing immunization at the furthest point from the immunosuppressing effect of cytotoxic treatment during a given cycle. In addition, a specific consideration to vaccination of children with acute lymphoblastic leukemia is the presence of polyethylene glycol (PEG) as a stabilizing component of mRNA COVID-19 vaccines, necessitating the development and validation of strategies to mitigate risk for children with a prior history of hypersensitivity to PEGasparaginase.…”
mentioning
confidence: 89%
“…Previous studies have shown lower prevalence and hospital admission rates in post-HSCT adults immunized with the influenza vaccine compared to those unimmunized [ 3 ]. Although there is a lack of data on children that have undergone HSCT, one study showed superior serologic response compared to age-matched controls for all vaccine strains [ 4 ]. However, there remains a paucity of data on the effectiveness and duration of seroprotection of the influenza vaccine in children, especially those that have undergone HSCT or chemotherapy.…”
Section: To the Editormentioning
confidence: 99%
“…50,51 noted that all pediatric transplant societies recognize that influenza vaccination is important to prevent severe disease, and recommend its prioritization as soon as possible in the influenza season. 21,52 Providers should note that use of antiviral medication at the time of LAIV (but not IIV) administration may impair response. 26 This is less likely to be a concern for pediatric transplant patients, as live virus vaccines are contraindicated for the majority of transplant recipients.…”
Section: Chemoprophyl a Xismentioning
confidence: 99%
“…Chemoprophylaxis should never be used as a substitute for vaccination—only as an adjunct measure—since immunization has significant benefits for individuals and the population as a whole, including decreased severity of illness if it does occur 50,51 . It should be noted that all pediatric transplant societies recognize that influenza vaccination is important to prevent severe disease, and recommend its prioritization as soon as possible in the influenza season 21,52 . Providers should note that use of antiviral medication at the time of LAIV (but not IIV) administration may impair response 26 .…”
Section: Chemoprophylaxismentioning
confidence: 99%